2021
DOI: 10.2196/20037
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to and Facilitators for Using Nutrition Apps: Systematic Review and Conceptual Framework

Abstract: Background Nutrition apps are effective in changing eating behavior and diet-related health risk factors. However, while they may curb growing overweight and obesity rates, widespread adoption is yet to be achieved. Hence, profound knowledge regarding factors motivating and hindering (long-term) nutrition app use is crucial for developing design guidelines aimed at supporting uptake and prolonged use of nutrition apps. Objective In this systematic revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
105
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(113 citation statements)
references
References 104 publications
8
105
0
Order By: Relevance
“…The cost of apps was cited as a significant factor among respondents. Interestingly, in line with prior related literature [ 34 , 35 ], most participants advocated that mHealth should be accessible (free) or more affordable. Additionally, limiting of advertisements, more food or dieting options, and the need for more personalized and goal-oriented features were also considered desired features for inclusion in mHealth apps.…”
Section: Resultsmentioning
confidence: 52%
“…The cost of apps was cited as a significant factor among respondents. Interestingly, in line with prior related literature [ 34 , 35 ], most participants advocated that mHealth should be accessible (free) or more affordable. Additionally, limiting of advertisements, more food or dieting options, and the need for more personalized and goal-oriented features were also considered desired features for inclusion in mHealth apps.…”
Section: Resultsmentioning
confidence: 52%
“…Some applications have merely provided dietary advice and improved the diet quality of participants; other applications monitor lapses and have the same effect on the user. Dietary applications that cause frustration to the user lead to complete disengagement, this can be in the form of draining the user's battery, poor data transfer or the app failing to work as detailed [64]. For the future of dietary applications, a focus on diet quality rather than goal-setting could have more significant long-term benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Along these lines, systematic reviews focusing on mHealth disease self-management interventions found that effective interventions integrated features of interactive communication [ 10 ] and tailored messages [ 22 ]. A systematic review of nutrition apps found that tailoring the apps to the needs of specific user groups can be beneficial in increasing engagement [ 23 ]. In addition, interventions can be more engaging if they are designed to be tailored to participants’ health beliefs and needs.…”
Section: Introductionmentioning
confidence: 99%